2017
DOI: 10.1007/s00122-017-2954-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification and mapping of ts (tender spines), a gene involved in soft spine development in Cucumis sativus

Abstract: Using map-based cloning of ts gene, we identified a new sort of gene involved in the initiation of multicellular tender spine in cucumber. The cucumber (Cucumis sativus L.) fruit contains spines on the surface, which is an extremely valuable quality trait affecting the selection of customers. In this study, we elaborated cucumber line NC072 with wild type (WT) hard fruit spines and its spontaneous mutant NC073, possessing tender and soft spines on fruits. The mutant trait was named as tender spines (ts), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 35 publications
2
34
0
Order By: Relevance
“…In addition, some LecRLKs affect the development and growth of plant, for instance, two L-type LecRLKs, LecRK-IX.1 and LecRK-IX.2 will induce cell death, thereby increasing plant survival, when infected with phytophthora (Wang et al, 2015). A C-type LecRLK mutant changed cell stacking pattern of trichome in cucumber, resulting fruit spines being easy to fall off from pericarp (Guo et al, 2017). It is similar to previous study (Yang et al, 2016), through the RNA-Seq data, we also found drastic number of CsLecRLKs may be expression in root (Fig.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, some LecRLKs affect the development and growth of plant, for instance, two L-type LecRLKs, LecRK-IX.1 and LecRK-IX.2 will induce cell death, thereby increasing plant survival, when infected with phytophthora (Wang et al, 2015). A C-type LecRLK mutant changed cell stacking pattern of trichome in cucumber, resulting fruit spines being easy to fall off from pericarp (Guo et al, 2017). It is similar to previous study (Yang et al, 2016), through the RNA-Seq data, we also found drastic number of CsLecRLKs may be expression in root (Fig.…”
Section: Discussionsupporting
confidence: 91%
“…Although there is only one subfamily member in Arabidopsis and rice, the C-type LecRLKs had not been reported involving any speci c biological traits for a long time. Until 2017, a C-type LecRLK was identi ed that may affect morphogenesis of trichome in cucumber (Cucumis sativus) (Guo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The mutant (Csts) used in this study was initially de ned as having a tender fruit spines [29]. With continuous tracking of the developmental stage of the fruit spines, we found that the most direct reason for the fruit spines being more easily bent was their developmental deformity in the mutant, which made the combination of the base and epidermis unstable (Fig.…”
Section: The Role Of Csts In the Development Of Cucumber Fruit Spinesmentioning
confidence: 99%
“…In the mutant, the expression levels of a series of calcium sensors were downregulated, which was closely related to the function of CsTs. CsTs is a C-type lectin receptor-like kinase located on the cell membrane [29]. The extracellular domain function of CsTs is serving as a calcium-dependent carbohydrate binding module.…”
Section: The Role Of Csts In the Development Of Cucumber Fruit Spinesmentioning
confidence: 99%
See 1 more Smart Citation